The Impact of City Branding, City Image, and Food Authenticity on Revisit Intention Mediated by Tourist Satisfaction - Sakti, Bima; Verinita; Maruf (SAFE-Network, 2024)
This research aims to determine the impact of city branding, city image, and food authenticity on intention to revisit, which is mediated by tourist satisfaction for domestics tourists who visit Payakumbuh City. This research is explanatory with quantitative methods. Meanwhile, the sampling technique used in this research was purposive sampling of tourists who visited Payakumbuh City at least twice, with a sample size of 165 respondents. This research uses PLS 4.0. The thing emphasized in this research is that the branding of Payakumbuh City as